Adapting to climate change in Eastern Europe and Central Asia - Fay, Marianne; Block, Rachel I.; Ebinger, Jane O. (World Bank e-Library., 2010)
The climate is changing and many Eastern European and Former Soviet Union countries are vulnerable to the consequences. Many countries are facing warmer temperatures, a changing hydrology and more extremes, droughts, floods, heat waves, windstorms, and forest fires. Already the frequency and cost of natural disasters have risen dramatically in the region. And the concentration of greenhouse gases already in the atmosphere guarantees that similar or greater changes are yet to come, even if the world completely stopped emitting carbon dioxide. Now, and at least for the near future, ECA vulnerabi.